Application of nanomaterials for removal of oil waste: review - Druzian, Daniel Moro; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
Petroleum is a difficult-to-remove chemical compound that leads to harmful environmental impacts when improperly discharged. In fact, this problem generates water, soil and air pollution, requiring advanced treatments such as photocatalysis, bioremediation and adsorption. In addition, nanomaterials make these techniques versatile and with a high percentage of contaminant removal. In this context, we seek to present a literature review on the main nanomaterials that can be used in the removal of petroleum residues. The research was carried out in the Web of Science database, where articles, books, theses and dissertations were selected, using the descriptors “nanoadsorption in Petroleum Waste” and “nanoadsorption in oils waste”. The results demonstrate that metallic nanomaterials using adsorption and photocatalysis processes present 50-60% removal of petroleum residue, as well as materials using bioremediation techniques present 50% of the removal of this residue. Based on the results found, it can be concluded that metallic nanomaterials for adsorption and photocatalysis present a high rate of elimination of organic compounds, being promising for the removal of this residue.